KORELASI ANTARA HITUNG TROMBOSIT DENGAN JUMLAH CD4 PASIEN HIV/AIDS - M. I. Diah Pramudianti; Tahono Tahono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
The Acquired Immune Deficiency Syndrome (AIDS) is the presence of symptoms caused by Human Immunodeficiency Virus (HIV)which belongs to human retroviruses (retroviridae). Thrombocytopenia is a common finding in patients with HIV infection. HIV infectionmay induce thrombocytopenia through immune and non-immune mechanisms, autoimmune combination and inhibition of plateletproduction. The aim of this study is to analyze the correlation between thrombocyte and CD4 count in HIV/AIDS patients. This studyuses a cross sectional design with a total of 17 patients. The subject of this study is HIV/AIDS patients who came to and examined atVCT clinic, dr. Moewardi Hospital Surakarta. To analyze this result the researchers used Spearman (r) correlation with p<0.05, andconfidence interval 95%. Patients’ median age was 30 (21–49) years, 11 (64.7%) men and 6 (35.3%) women. The subjects with AIDSwere 11 (64.7%), and HIV were 6 (35.3%) patients. The duration of antiretroviral (ARV) was 7.5 (4–20) months in 10 subjects.The median of thrombocyte count was 203 (143–327)×103/μL, CD4 absolute 207 (5.0–734)/μL, and CD4 (% lymphocytes) 13.0(2.0–29.0)%. The thrombocyte count was not correlated with CD4 absolute (r=0.456; p=0.066) and CD4% (r=0.218; p=0.400). InHIV patients, low platelet counts will be the result of a host of problems and complications that are associated with the progressive HIVinfection or its management.